Extraversion as a moderator of resilience factors in lesbian, gay, and bisexual adults. Issue 1 (2nd January 2018) - Tse, Joseph; Kwon, Paul; Faust, Emily
ABSTRACT: The present study aims to replicate and expand findings from a prior study that examined whether extraversion moderates the beneficial effects of resilience factors of social support and emotional openness among sexual minorities. We recruited 389 lesbian, gay, and bisexual adults. Participants completed a series of measures on extraversion, social support, emotional openness, and depression online. Among lesbian, gay, and bisexual adults, depressive symptoms were negatively associated with extraversion, social support, and emotional openness; extraversion did not moderate the relationship between social support and depressive symptoms. When isolating the sample of lesbian and bisexual women, extraversion did not moderate the relationship between emotional openness and depressive symptoms. Conversely, when isolating the sample of gay and bisexual men, extraversion moderated the relationship between emotional openness and depressive symptoms, such that emotional openness was associated with fewer depressive symptoms at low levels of extraversion. Social support and emotional openness enhance the resilience against depression for sexual minorities. Gay and bisexual men with low levels of extraversion could particularly benefit from emotional processing. Clinical implications are discussed.